DURING THE FIRST WORLD WAR GERMANY AND AUSTRIA – HUNGARY PRISONERS OF THE AULIEATA COUNTY - Apendiyev T.А.,; Abdukadyrov N.М., (Scientific Journal of Pedagogy and Economics, 2020)
The First World War was the largest event in the history of mankind, which had a significant impact on the fate of many peoples, including states. One of the main factors was the capture of troops and individuals on the front of the war between warring states and the flight of soldiers as a result of the war. During the war, neighboring states, political allies captured each other's armies and citizens. The capture of citizens of each other took place between the Entente and the central powers. The Russian Empire, which was part of the Entente and was considered the main participant in the war, detained people from the central powers. Citizens of the central powers captured during the war were sent to all regions of the Russian Empire, which also extended to the steppe and Turkestan provinces. Based on this, the Turkestan Territory was considered one of the key regions of the Russian Empire, in which Europeans were accepted. In the era of the empire, European prisoners lived in the Aulieata district of the Turkestan governor general in the SyrDarya region. Representatives of European nationality have lived in the region since the end of the nineteenth century, and this continued during the years of the First World War. During World War I, the Aulieatа district was considered one of the districts where European prisoners and refugees were received. Although the number of prisoners of war from the central powers (Germany, Austria-Hungary) in the Aulieatа district is small, traces of political prisoners of war still remain from these states. The article discusses the history of prisoners of war deported to Aulieata district during the war years. The socio-political status of the citizens of Germany and Austria-Hungary who arrived in Aulieatа County, their life is studied. The nationality and surname of the captives will be determined, and their standard of living will be determined.